Єдиний інформаційний простір: формування та застосування у сфері забезпечення безпеки дорожнього руху в Україні - Микулець, В.; Mykulets, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті проаналізовано поняття «єдиний інформаційний простір» і інтерпретовано його зміст до потреб нормативно-правового забезпечення дорожнього руху в Україні, визначено особливості формування та застосування його в сфері забезпечення безпеки дорожнього руху. Встановлено, що єдиний інформаційний простір безпеки дорожнього руху України існує як органічна складова світового і європейського інформаційних просторів, що поєднує ефективне застосування транскордонної інформаційної інфраструктури, врахування національних інтересів і економічної доцільності, підтримання належного рівня інформаційної безпеки. The article analyzes the concept of «unified information space» and interprets its content to the needs of normative and legal support of traffic in Ukraine, determines the features of the formation and its application in the area of the traffic safety. It was established that unified information space of the traffic safety in Ukraine exists as an organic component of the global and European information space, combining effective use of cross-border information infrastructure, considering the national interests and economic expediency, maintaining an appropriate level of information security. The structure of the unified information space of the traffic safety in Ukraine includes: information resources to support the traffic safety; informational and telecommunication infrastructure of the traffic safety; the system of the organization of information’s protection and defense as a components of a higher level system - information security in road traffic.
Unified Information Space: Formation and Application in the Area of Traffic Safety in Ukraine
Keywords: інформація; інформаційне суспільство; єдиний інформаційний простір; безпека дорожнього руху; державтоінспекція; information; information society; unified information space; traffic safety; state traffic inspectorate